Design of Livestock Chicken Information System in CV Cilacap Indah Abadi, Kebumen Regency Based on Website - Akhmad Fatoni; Candra Mecca Sufyana (Politeknik Piksi Ganesha Indonesia, 2021)
CV Cilacap Indah Abadi is a company established in chicken stock. This company cooperates with several suppliers and chicken breeders spread across several sub-districts in Kebumen Regency. In addition to providing farm chickens, CV CIA also provides feed and medicine. This company still uses handwritten or manual recording, causing the process of company management, especially in the inventory field, to take a long time and is less efficient. Underlying the problem above, the company needs an information system that facilitates company performance based on/using a website to store records in the database. The research results are in a website application for poultry stock systems using/based on the CodeIgniter 3.1 framework.